Dominikanerorden, Archiv. Wien-hez - Irmédi-Molnár László (Fond 165 Irmédi-Molnár László, 1963)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Irmédi-Molnár László levelezése. > Irmédi-Molnár László levélfogalmazványai